2012
DOI: 10.1186/1756-0500-5-390
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin in the pathogenesis of hepatocellular carcinoma complicating chronic hepatitis C: an immunohistochemical and PCR study of human liver biopsies

Abstract: BackgroundThe possible role of secretory products of fibrous tissue in the development of hepatocellular carcinoma (HCC) complicating chronic hepatitis C was investigated. Our hypothesis was that gremlin, secreted by fibroblasts, inhibited bone morphogenic protein (BMP), which mediates stem cell maturation into adult functioning hepatocytes, and thus, arrest stem cell maturation and promoted their proliferation in an immature state possibly culminating into development of HCCs.ResultsProtein expression of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…The antinociceptive efficacy of HBO treatment has been proven in many rodent experiments and also human patients [911, 13]. In accordance with these findings, our current study demonstrated that five consecutive days of HBO treatment greatly attenuated neuropathic pain by suppressing hypersensitivity in rats following CCI of the sciatic nerve.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The antinociceptive efficacy of HBO treatment has been proven in many rodent experiments and also human patients [911, 13]. In accordance with these findings, our current study demonstrated that five consecutive days of HBO treatment greatly attenuated neuropathic pain by suppressing hypersensitivity in rats following CCI of the sciatic nerve.…”
Section: Discussionsupporting
confidence: 89%
“…Emerging lines of evidence suggest that HBO therapy can reduce chronic pain in animal models [911]. In addition, the use of HBO treatment has been proven to attenuate chronic cluster headaches and [12] idiopathic trigeminal neuralgia in patients [13]. Our previous study indicated that the antinociceptive effects of HBO therapy may be linked to inhibition of astrocyte activation and inflammation in a chronic constriction injury (CCI)-induced neuropathic pain model in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in chronic hepatitis C associated HCC, activation of FGF signaling is observed [128, 129] and increased FGF levels are associated with enhanced HCV replication and release of infectious particles [130]. Cross talk of Wnt and FGF pathways in HCV-related HCC is supported by observations that FGF signaling leads to the release of β-catenin from the β-catenin–E-cadherin complexes because of the phosphorylation of Tyr654 as described above.…”
Section: Wnt/β-catenin Signaling Paves the Way For Progression Of Chrmentioning
confidence: 99%
“…CK19 is used to assess severity of liver disease and fibrosis deposition in some hepatic disorders [47,48]. In this study, CK19 expression was lower in the hiHIF2a and loVEGFR2 subsets.…”
Section: Discussionmentioning
confidence: 91%